2013
DOI: 10.1073/pnas.1303829110
|View full text |Cite
|
Sign up to set email alerts
|

Generation of induced neurons via direct conversion in vivo

Abstract: Cellular reprogramming is a new and rapidly emerging field in which somatic cells can be turned into pluripotent stem cells or other somatic cell types simply by the expression of specific combinations of genes. By viral expression of neural fate determinants, it is possible to directly reprogram mouse and human fibroblasts into functional neurons, also known as induced neurons. The resulting cells are nonproliferating and present an alternative to induced pluripotent stem cells for obtaining patient-and disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
326
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(341 citation statements)
references
References 27 publications
7
326
0
8
Order By: Relevance
“…8 Torper's study showed that human fibroblasts and astrocytes could be transplanted and converted into neurons when specific genes were activated. 27 In addition, Torper also found that mouse astrocytes could be directly reprogrammed into neurons with nuclear expression in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…8 Torper's study showed that human fibroblasts and astrocytes could be transplanted and converted into neurons when specific genes were activated. 27 In addition, Torper also found that mouse astrocytes could be directly reprogrammed into neurons with nuclear expression in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…[36,37]. Il est donc tout à fait envisageable que les cellules reprogrammées aient eu pour origine des astrocytes réactionnels plutôt que quiescents.…”
Section: Les Glies Candidats Favoris à La Reprogrammation Neuronaleunclassified
“…Ascl1 [39] Sox2 ± VPA [41] Fezf2 [42,43] Neurog2 + FGF2/EGF [40] Neurog2 + FGF2/EGF [40] Sox2 + BDNF/VPA [37] Ascl1, Brn2, Mytl1 [36] NeuroD1 [33] NeuroD1 [33] Gliose réactionnelle [43]. Nous montrons que Fezf2 suffit à reprogrammer les neurones calleux postmitotiques en neurones corticofugaux, exprimant en combinaison les marqueurs spécifiques des couches corticales V et VI, et capables de projeter leurs axones vers des cibles sous-corticales (thalamus) et sous-cérébrales (moelle épinière), typiques des neurones des couches VI et V du cortex, au détriment des connexions corticales (via le corpus calleux) normalement établies par les neurones ciblés [43] (Figure 1C).…”
Section: Sox2unclassified
“…Transdifferentiation is the conversion of a differentiated cell to alternative lineage(s), such as conversion from fibroblasts to neurons [94][95][96][97]. Regarding glial cells, we have previously shown that activation of the JAK/STAT signalling pathway can induce transdifferentiation from oligodendrocytes into astrocytes [98].…”
Section: (B) Towards Reprogramming To or From Neuronsmentioning
confidence: 99%